2009
DOI: 10.1084/jem.20090545
|View full text |Cite
|
Sign up to set email alerts
|

Loss of SOCS3 expression in T cells reveals a regulatory role for interleukin-17 in atherosclerosis

Abstract: Atherosclerosis is an inflammatory vascular disease responsible for the first cause of mortality worldwide. Recent studies have clearly highlighted the critical role of the immunoinflammatory balance in the modulation of disease development and progression. However, the immunoregulatory pathways that control atherosclerosis remain largely unknown. We show that loss of suppressor of cytokine signaling (SOCS) 3 in T cells increases both interleukin (IL)-17 and IL-10 production, induces an antiinflammatory macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
252
2
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(274 citation statements)
references
References 37 publications
11
252
2
8
Order By: Relevance
“…Moreover, its role in vascular dysfunction such as atherosclerosis is controversial 45, 46, 47. According to Madhur et al ., IL‐17A is necessary to induce superoxide vascular production in response to a high fat diet in ApoE −/− mice 48.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, its role in vascular dysfunction such as atherosclerosis is controversial 45, 46, 47. According to Madhur et al ., IL‐17A is necessary to induce superoxide vascular production in response to a high fat diet in ApoE −/− mice 48.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis and its consequences (i.e., myocardial infarction and stroke) remain the major cause of morbidity and mortality in Western countries. Several studies have investigated the role of IL-17A in the development of atherosclerosis with partially controversial results (7)(8)(9)(10)(11)(24)(25)(26), which are at least partially based on the study design, neutralizing Ab versus bone marrow transfer experiments, on the type of diet, and on the location of the analysis of the atherosclerotic lesion. By contrast, the current study evaluated the role of IL-17A on advanced atherosclerotic lesions and its potential impact as a therapeutic target.…”
Section: Synergistic Effects Of Il-17a In Addition To Lps In the Plaqmentioning
confidence: 99%
“…IL-17A is produced by various inflammatory cells, including T cells and macrophages, and modulates the expression of several proinflammatory molecules (TNF-a, IL-1b, and CCL2 [MCP-1]) and matrix metalloproteinases (5,7). Previously, our group and others (7)(8)(9)(10)(11) have shown that inhibition of IL-17A influenced atherosclerotic lesion development in mice with partially controversial results. Because the highest expression rates of IL-17A were observed in human carotid artery plaques derived from symptomatic patients with stroke or transient ischemic attack (12,13), IL-17A may be linked to vulnerability of human atherosclerotic lesions.…”
mentioning
confidence: 99%
“…The role of Th17 in atherosclerosis is also debated as conflicting reports exist (30)(31)(32). In contrast to CD4 + T helper cells, CD8 + cytolytic T lymphocytes have not been extensively studied, even though CD8 + T cells are abundant in atherosclerotic plaques and they have been shown to be activated in hypercholesterolemic Apoe -/-mice (33).…”
Section: T Cells Modulate Inflammation In Atherosclerosismentioning
confidence: 99%